Formamide based monomer for highly functionalized polymers. Issue 1 (9th November 2021) - Chen, Ri; Ayyakkalai, Balamurugan; Sun, Jian; Lee, Gene A.; Gopalan, Padma
Abstract: Multicomponent reactions (MCRs) are widely used in organic chemistry to simplify the synthesis of highly functionalized molecules in a single‐pot reaction. However, their utility for polymer post‐functionalization is severely limited due to the complexity of handling highly reactive and unpleasant isocyanide compounds. In this work, we present a stable methacrylate monomer 2‐formamido ethyl methacrylate (FEMA) containing a benign formamide group that can be converted to isocyanide in situ and that can undergo MCRs in a one‐pot protocol. Block and random copolymers of FEMA with methyl methacrylate were tested for efficiency in MCRs. As a function of composition and architecture, MCR conversions of >90% was achieved in the polymers. This benign bench stable monomer allows incorporation of complex functionality in a one‐pot synthesis to the polymer sidechain using MCRs without direct handling of the isocyanide monomers and polymers. Abstract :